OPTIMIZING CIGS SOLAR CELL PERFORMANCE: THE IMPACT OF COUNTER ELECTRODE ON ELECTRODEPOSITION METHODS - Rahmawati, Hilda; Ismail, Nurmalasari (Indonesian Physical Review, 2024)
Copper Indium Gallium Selenium (CIGS) is a type of solar cell with great potential to be developed to meet increasing energy needs. Electrodeposition is the preferred technique for fabricating CIGS solar cells because it is simple, does not require vacuum equipment, and is low-cost. One factor influencing electrodeposition is the counter electrode, so in this research, CIGS will be fabricated using platinum wire and platinum plate as the counter electrode. Based on the XRD results of CIGS oriented at (112), (211), (220), and (312), the UV-Vis results show that the resulting CIGS has an absorbance peak of 390 nm. CIGS solar cell performance results based on photoresponse produce 0.99 s and 0.45 s when using platinum wire and plate consecutively. Both platinum wire and plate as counter electrodes in electrodeposition can produce CIGS solar cells. However, CIGS with a platinum plate as a counter electrode produces more optimal CIGS performance.